2009
DOI: 10.22146/gamaijb.5525
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ Perceptions on the Objectives, Characteristics and Selection Criteria of Islamic Bank in Thailand

Abstract: Due to relatively new establishment of islamic bank in Thailand and paucity of empirical research undertaken in the area, this study intends to capture the perceptions of Thai customers towards the objectives and characteristics of the islamic bank. In addition, this study aims to determine the important bank selection criteria as perceived by the customers and the differences in the perceptions of moslem and non-moslem customers were identified. The study surveys a sample of 462 respondents. The empirical fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
5
22
0
1
Order By: Relevance
“…At the basic level, however, consumers do not differentiate between the image of a conventional bank and that of an Islamic bank. Thai consumers perceive the social image of the Islamic banks as an important consideration as compared to the conventional banks(Lateh, Ismail, & Ariffin, 2009). Recently,Tara, Irshad, Khan, Yamin, and Rizwan (2014) analysed the performance of Islamic banking in Pakistan.…”
mentioning
confidence: 99%
“…At the basic level, however, consumers do not differentiate between the image of a conventional bank and that of an Islamic bank. Thai consumers perceive the social image of the Islamic banks as an important consideration as compared to the conventional banks(Lateh, Ismail, & Ariffin, 2009). Recently,Tara, Irshad, Khan, Yamin, and Rizwan (2014) analysed the performance of Islamic banking in Pakistan.…”
mentioning
confidence: 99%
“…There are some specific studies on the awareness and perception of financial products among bank customers. Lateh et al (2009) in their research on the awareness of the customers towards financial products of Islamic bank concluded that most of the Thai customers were aware of financial products of Islamic bank but their understanding level about the products was low when it is compared to other countries. In Pakistan, the customers were aware of some general products such as time deposit and current accounts (Khattak andRehaman, 2010 andOkumus, 2005).…”
Section: Literature Review (A) Awareness and Understanding Of Finmentioning
confidence: 99%
“…Previous studies on the Islamic banks' preferences have been intensively conducted in Malaysia (Haron at al., 1994;Amin and Isa, 2008;Dusuki and Abdullah, 2007;Abdelghani andOladokun, 2012, Haque et al, 2009), Jordan (Erol andEl-Bdour, 1989, Kamal et al, 1999), Bangladesh (Hassan et al, 2007), Bahrain (Al-Ajmi et al, 2009), Thailand (Lateh et al, 2009), and UK (Walid et al, 2010). Similar studies have also been conducted in the Indonesia (Anam, 2006;Efendi, 2008;Maski, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%